Lower extremity and carotid artery disease in COPD. Issue 4 (26th October 2016) - Pizarro, Carmen; Linnhoff, Fabian; van Essen, Fabian; Pingel, Simon; Schaefer, Christian Alexander; Schahab, Nadjib; Fimmers, Rolf; Nickenig, Georg; Skowasch, Dirk
In view of their common chronic inflammatory process, we sought to determine the linkage between peripheral artery disease and chronic obstructive pulmonary disease (COPD). 107 COPD patients (mean±sd age 64.6±10.4 years, 52.2% male) and 22 control smokers without previously diagnosed peripheral artery disease underwent standardised angiological examination for lower extremity artery disease (LEAD) and carotid artery disease. LEAD was significantly more prevalent in COPD patients than in controls (80.4% versus 54.5%, p=0.002). Among COPD patients, 57.0%, 12.2%, 10.3% and 0.9% were found to be in Fontaine stages I, IIA, IIB and III, respectively. As with carotid artery disease, its frequency increased from 36.4% in controls to 58.9% in COPD patients (p=0.003). Carotid plaque burden, LEAD Fontaine degrees as well as pulse wave index and ankle–brachial index manifested significant impairment over percentage predicted forced expiratory volume in 1 s (FEV1 % pred) (p=0.02, p<0.001, p=0.01 and p<0.001, respectively). Multivariate analysis revealed that COPD Global Initiative for Chronic Obstructive Lung Disease status was the strongest independent predictor for the presence of plaque in lower extremity arteries (odds ratio 1.63, 95% CI 1.19–2.25, p=0.003) and carotids (odds ratio 1.66, 95% CI 1.14–2.44, p=0.009). As compared with control smokers, peripheral artery disease is diagnosed in a sizeable proportion of COPD patients and exhibits significant distributive differences over FEV1 % pred that exceed the susceptibility conferred by common cardiovascular stressors. Undiagnosed lower extremity and carotid artery disease is common in COPD and aggravates over COPD GOLD stages http://ow.ly/w96f303lHTu